1997
DOI: 10.2527/1997.75113038x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen metabolism and hormonal responses of steers fed wheat silage and infused with amino acids or casein.

Abstract: Four Holstein steers (159 kg) surgically fitted with abomasal-infusion cannulas were used in a 4 x 4 Latin square study to test amino acid (AA) and casein (CAS) infusions on nitrogen balance and hormonal status of steers consuming vegetative wheat (Triticum aestivum L.) silage (12.3% CP). Treatments were 5-d infusions of 1) water (CONT), 2) arginine (ARG; 13.69 g/d), 3) limiting amino acids (LAA, 13.69 g/d arginine + 10.92 g/d histidine + 28.97 g/d lysine + 10.88 g/d methionine + 16.96 g/d threonine, and 4) Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
1
18
1
Order By: Relevance
“…Treatment 1 did not contain Na- tively. This experiment also confirms that digestible AA complements can have biological values higher than 1.0 (Storm and Ørskov, 1984;Ragland-Gray et al, 1997). Here, the infusion of 1.6 g/d of N (in Met form) improved N retention 11-fold.…”
Section: Methodssupporting
confidence: 70%
“…Treatment 1 did not contain Na- tively. This experiment also confirms that digestible AA complements can have biological values higher than 1.0 (Storm and Ørskov, 1984;Ragland-Gray et al, 1997). Here, the infusion of 1.6 g/d of N (in Met form) improved N retention 11-fold.…”
Section: Methodssupporting
confidence: 70%
“…Higher plasma insulin concentrations were observed after abomasal casein infusion in steers (Guerino et al, 1991;Ragland-Gray et al, 1997;Robinson, 1998) and lambs (Beermann et al, 1991). However, we did not observe an increase in glucose, NEFA or insulin (P > 0.05).…”
Section: Discussionmentioning
confidence: 38%
“…This is in agreement with McGuire et al (1992), who found that with increased dietary crude protein, given to lactating dairy cows, plasma insulin was higher but there was no increase in plasma glucose and NEFA. Similarly, Guerino et al (1991) and Ragland-Gray et al (1997) found higher plasma insulin after the infusion of casein into the abomasum in steers. But, Knaus et al (2002) observed that plasma glucose and NEFA in growing cattle did not increase when the protein in the diet increased.…”
Section: Discussionmentioning
confidence: 84%